Satisfaction of European Tourists – Benchmarking of EU Countries - Štumpf, Petr; Vojtko, Viktor; Valtrová, Barbora (People and Global Business Association, 2018)
High level of satisfaction of tourists is one of the most common goals of sustainable tourism destinations. The general assumption is that higher level of tourists' satisfaction leads to a higher tourists' loyalty to destinations. This research looks on this relationship from macro level of European Union (EU) countries. We have used data from Eurobarometer – Preferences of Europeans towards Tourism between 2013 and 2016 – to statistically compare and analyse several satisfaction indicators of European tourists incoming the chosen EU countries. The results show significant differences amongst countries as destinations and could be used to identify strengths and weaknesses of EU countries as tourism destinations. The robust data set enables the benchmarking of EU countries as tourism destinations from the tourists' satisfaction point of view. This study shows the ranking of the EU countries in several dimensions of tourists' satisfaction.
Spokojenost evropských turistů - benchmarking zemí EU
Keywords: Tourism; Satisfaction; Eurobarometer; EU countries; Benchmarking; turismus; spokojenost; Eurobarometer; země EU; benchmarking